2009
DOI: 10.1063/1.3257381
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostructural coupling and magnetocaloric effect in Ni–Mn–In

Abstract: Magnetic-field-induced martensitic phase transition and the concomitant change of volume are investigated in Ni-Mn-In alloy. A well-defined linear relationship is found between the quantity characterizing magnetic degree of freedom and the thermal expansion on behalf of structural degree of freedom, which demonstrates the magnetostructural coupling. Within the exchange-inversion model, such a linear relationship is theoretically derived and the magnetostructural correlation is elucidated. The lattice-entropy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…In Fig. 2͑a͒, the pattern measured at 340 K confirms the co- Ni-Mn-In, 12 it is reasonable to assume that, for the sample with 0 Ͻ x Յ 0.25, the smaller distance between the Mn and Co sublattices below T t favors the AFM state whereas the relatively larger distance above T t is suitable for the FM arrangement of the magnetic moments. Because the contribution of electronic entropy change ͑⌬S E ͒ is very small, the ⌬S M for a FOMST mainly consists of the spin-entropy change ͑⌬S spin ͒ plus the lattice-entropy change ͑⌬S L ͒.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…In Fig. 2͑a͒, the pattern measured at 340 K confirms the co- Ni-Mn-In, 12 it is reasonable to assume that, for the sample with 0 Ͻ x Յ 0.25, the smaller distance between the Mn and Co sublattices below T t favors the AFM state whereas the relatively larger distance above T t is suitable for the FM arrangement of the magnetic moments. Because the contribution of electronic entropy change ͑⌬S E ͒ is very small, the ⌬S M for a FOMST mainly consists of the spin-entropy change ͑⌬S spin ͒ plus the lattice-entropy change ͑⌬S L ͒.…”
mentioning
confidence: 81%
“…16 For the martensitic transition in Ni-Mn-In alloys, the contribution of ⌬S L has been estimated at about 50% of ⌬S M . 12 For Gd 4 Si x Ge 4−x , this contribution is found to be lower, varying from 20% to 40%. 17 In Mn 1−x Cr x CoGe, the amount of orth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В целом ха-рактер и значения относительных изменений линейных размеров образцов с 0 ≤ x ≤ 3 при мартенситном пре-вращении сравнимы с наблюдавшимися в классических сплавах Гейслера с магнитной памятью формы на ос-нове системы Ni−Mn−Ga [17,18]. Для новых сплавов Гейслера на основе сплавов системы Ni−Mn−Sn нам не удалось найти в литературе экспериментальных дан-ных об изменении размеров при мартенситном пре-вращении, а в сплавах Ni−Mn−In линейные размеры образца могут увеличиваться при фазовом переходе мартенсит−аустенит на 0.25% [19].…”
Section: рисunclassified
“…[55,63,69,70] Furthermore, Li et al investigated the magnetostructural coupling in Ni 50 Mn 35 In 15 systems and identified the contribution of the lattice-entropy change to the total entropy change. [64] Very recently, Liu et al demonstrated that the structural transition plays a dominant role for the considerable adiabatic temperature change in the metamagnetic NiMnCoIn alloys. [15] Here we mainly review our recent progress with regard to the effects of atomic substitution, post-annealing, the introduction of interstitial atoms, and forced atomic disorder on the magnetic, magnetocaloric, and transport properties of the novel NiMn-based metamagnetic Heusler alloys.…”
Section: Magnetic Entropy Change In Conventional Nimn-based Heusler Amentioning
confidence: 99%